Processes and pathways mediating the experience of social anxiety and negative rumination. (April 2018) - Modini, Matthew; Rapee, Ronald M.; Abbott, Maree J.
Abstract: Negative rumination in social anxiety disorder (SAD) occurs in anticipation of a social event (pre-event rumination) and in its aftermath (post-event rumination). Both are proposed to be key maintaining factors of the vicious cycle of social anxiety. Despite this, there is a dearth of research investigating the processes that mediate the relationship between social anxiety and pre-event rumination and uncertainty regarding the cognitive and attentional processes that mediate the relationship between social anxiety and post-event rumination. To investigate this further, the current study utilised a clinical sample of participants with SAD to determine the hypothesised mediators of a social anxiety and pre-event model (N = 239) and a social anxiety and post-event rumination model (N = 216). Results from path analyses were broadly consistent with cognitive models of SAD that posit several interrelated processes mediate the relationship between social anxiety and pre- and post-event rumination. Results also indicated slightly different processes showed stronger prediction of pre-event rumination (i.e., biased performance appraisals) and post-event rumination (i.e., negative attentional focus). Treatment recommendations that aim to address the maladaptive role of negative rumination in social anxiety are made in keeping with the inter-connected and dynamic role played by cognitive and attentional processes in heightening social anxiety. Highlights: Mediators of the social anxiety and rumination relationship are investigated. Path analyses indicate several interrelated processes mediate this relationship. Pathways of processes somewhat differ in pre- and post-event rumination models.